Strange spirits and even stranger bodies L'icona di Elizabeth 1 nelle biografie di tre modernisti inglesi - Viviani, Aglaia (Scuole di dottorato, 2003)
The book examines the works of three English modernists also dealing with the iconic figure of Elizabeth Tudor. They are works focusing on the queen by Giles Lytton Strachey ("Elizabeth and Essex") and Edith Sitwell ("Fanfare for Elizabeth" and "The Queens and The Hive") and the biographical sketches written by Virginia Woolf in "Orlando" and in some short stories. The figure of the queen is seen as biographical object/subject of the biographers who write about her, investigating her gender in a new way thanks to the tools provided by Freudian studies.